Tidal Exclusion Barriers Fragment an Invertebrate Community into Taxonomically and Functionally Distinct Estuarine and Wetland Assemblages - Sorcha Cronin-O’Reilly; Alan Cottingham; Linda H. Kalnejais; Kath Lynch; James R. Tweedley (Journal of Marine Science and Engineering)
Various types of tidal barriers are used in estuaries to reduce saltwater intrusion and regulate freshwater discharge, but they often alter the physicochemical environment and faunal composition. With the use of these structures expected to increase due to climate change, there is a need to understand their impacts. A tidal exclusion barrier in the Ramsar-listed Vasse–Wonnerup Estuary (Australia) was found to act as an ecotone, fragmenting the estuarine gradient into two distinct components, a relatively stable marine-like environment downstream and a highly variable oligohaline to hypersaline (~0 to >100 ppt) environment upstream. The downstream regions contained a speciose and functionally rich estuarine fauna, comprising mainly polychaetes and bivalves. The upstream regions were taxonomically and functionally depauperate, containing insects, gastropods, and ostracods typically found in saline wetlands. The fragmentation of the estuary has likely impacted the provision of ecosystem services, with the fauna downstream mainly comprising burrowing species that bioturbate and, thus, aid in nutrient cycling. In contrast, the environmental conditions caused by the barrier and the resultant epifaunal invertebrate assemblages upstream aid little in bioturbation, but provide nutrition for avian fauna. These results may help in understanding the impacts of constructing new barriers in coastal ecosystems in response to climate change.